A firm level analysis of asymmetric response of U.S. stock returns to exchange rate movements. (21st August 2020) - Salisu, Afees A.; Isah, Kazeem; Ogbonnaya‐Orji, Nnenna
Abstract: The extant studies on stock returns–exchange rate nexus have been suspected of aggregation bias, we therefore resolve to revisit the nexus using firm‐level data while also accounting for asymmetry. We utilize stock price data covering 326 firms listed in S&P500 index and organized into 11 sectors. We examine the probable asymmetric response of these firms to exchange rate movements using the nonlinear panel ARDL method which simultaneously accounts for any inherent asymmetry and heterogeneity effects and suitable for large N and Large T panels. We establish that asymmetry exists in the stock returns–exchange rate nexus predominantly in the short run. We further show that exchange rate appreciation (depreciation) produces primarily positive (negative) effects on stock returns. We also find that the positive impacts overwhelm the negative impacts in magnitude and statistical significance. Thus, returns on investment in U.S. stocks differ significantly between currency appreciation and depreciation and by implication investors seeking to maximize returns need to exercise some level caution when confronted with sharp swings in exchange rate particularly during turbulent periods. While the results are robust to data frequency and to an extent, the choice of foreign currency, they are sensitive to different market conditions.